Meninjau Kembali Mekanisme Hukum dan Reforma Agraria dalam Menangani Mafia Tanah di Indonesia: Kasus Nirina Zubir - Ayu Nurhidaya; Gina Dwi Sari; Dian Susantini (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study reexamines the legal mechanisms and agrarian reform framework in addressing land mafia practices in Indonesia, focusing on the Nirina Zubir case. The research adopts a normative juridical approach using statutory, conceptual, and case analyses to assess the alignment between legal norms and practical implementation. Findings reveal that although Indonesia’s legal framework—anchored in the Basic Agrarian Law and ministerial regulations—is well established, enforcement remains hindered by overlapping institutional authority, weak bureaucratic integrity, and a fragmented land administration system. Agrarian reform has not yet operated as an effective preventive instrument, as it remains focused on redistribution rather than structural legal reform. The study recommends full digitalization of the land registry, public audits of agrarian institutions, enhanced bureaucratic integrity, and a stronger synergy among criminal, civil, and administrative laws. The integration of agrarian reform and legal mechanisms is essential to dismantle systemic loopholes exploited by land mafias and to reinforce social justice and legal certainty in Indonesia’s land governance.